Walking off the beaten path: Everyday walking environment and practices in informal settlements in Freetown. (September 2021) - Oviedo, Daniel; Okyere, Seth Asare; Nieto, Mariajosé; Kita, Michihiro; Kusi, Louis Frimpong; Yusuf, Yasmina; Koroma, Braima
Abstract: Walking is the dominant mode of transport in informal settlements of the global south, especially in African cities where structural deficits, morphological challenges and ineffective urban development constrains sustainable transport planning for low-income areas. Despite emerging scholarship on walking in Africa, the literature pays little attention to everyday realities of the walking environment. This paper presents preliminary results of a pilot study that examined the walking environment and everyday walking practices in an informal settlement in Freetown, Sierra Leone, using web-based mapping and a qualitative questionnaire. The results show that walking remains the predominant means of mobility in the settlement mainly as a result of the topography and poor infrastructure. Residents have resorted to improvisations through self-constructed routes to mitigate risks and improve walking experiences, as well as self-provided street lights or benches for rest stops. Our results show that local improvisations influenced residents' positive experiences of walking. The paper highlights the need for collaborative and participatory local interventions that are built on everyday walking practices to support co-production methodologies for understanding and improving local walking experiences. Through context-specific understandings of the everyday walking environment, the research provides avenues for urban transport and development planners to work with local actors for improving accessibility in informal urban neighbourhoods facing acute structural deficits for urban mobility and access to essential everyday services.